Food Insecurity in Perú: a multidisciplinary approach to a problem rooted in society - Quispe-Villanueva, Manuel (2023)
Science and technology applied to food provide great expectations for human health, however, global climatic, political and socio-economic situations endanger food security at the global and local levels, which is why the objective was to carry out a situational diagnosis of our country regarding the risks of food insecurity and make some suggestions that contribute to public policies and management. The methodology used was documentary; journals such as Nature, Science, American Journal of Climate Change, Scielo and the academic Google web page were reviewed. We also reviewed journalistic reports and web pages of different public institutions. In all cases we used the key words food security. It was concluded that Peru has no policy or public management for food security of the population in general for situations of natural disasters or others.